Prospective study of 50 cases of perforative peritonitis a single centre experience - Patel, Prakash B.; Baria, Suryadeep (International Surgery Journal, 2017)
Background: Perforative peritonitis are most common surgical emergencies seen worldwide. Despite improvement in diagnosis, antibiotics, surgical treatments and intensive care support, it is still an important cause of mortality in surgical patients. This study was done to know the spectrum of etiology, clinical presentation, management and treatment outcomes of patients admitted with perforation peritonitis in our hospital. Methods: A prospective study was done over a period of 3 years from January 2007 to December 2010 in NHL Medical College and V.S. hospital, Ahmedabad which included 50 patients diagnosed with perforation peritonitis. All patients admitted with perforation of gastrointestinal tract were included in this study. All cases of primary peritonitis and anastomotic leaks were excluded from this study. Results: Total 50 cases were included with 80% being males. Highest incidence of perforation peritonitis was noted in 21-30 years of age group in the present study. Most common etiology of perforative peritonitis was noted in the present study was peptic perforation 40% (20) cases, abdominal pain, tenderness were present in all of the perforative peritonitis patients. Conclusions: Perforative peritonitis is more common in male and most common pathology was peptic perforation due to acid peptic disease, in most of the cases after adequate resuscitation and stabilization of the patient Exploratory laparotomy is mainstay treatment modality